Shear Capacity of RC Beam with Opening Strengthened Using CFRP Sheet and Plate - Moi Kin Fai; Noorwirdawati Ali (International Journal of Sustainable Construction Engineering and Technology, 2024)
This paper investigates the use of carbon fibre-reinforced polymer (CFRP) sheets and plates for the bi-directional reinforcement of reinforced concrete beams with transverse single and double symmetrical openings. The dimensions of the under-reinforced specimens are 1900mm in length, 150mm in width, and 300mm in height, with 3H12 tension reinforcement, 2H6 compression reinforcement, and R6-300 stirrups. This study aims to compare the maximal shear capacity of each CFRP configuration to that of conventional beams and evaluate the deflection profiles, failure modes, strain distribution, and crack patterns under shear loads. The beams are created using in-situ casting, and the openings are treated using post-drilling techniques to simulate real-world procedures. The beam specimens are subjected to a four-point stress test following the application of Sikadur-330 and CFRP. The principal findings indicate that the application of CFRP sheets increases the ultimate shear strength compared to conventional beams with openings, whereas the application of CFRP plates has the opposite effect. Nevertheless, the control beam with no openings has the greatest ultimate shear capacity. In addition, the sheet reinforced CFRP specimens exhibit less deflection than the control beam and conventional beams. Using both CFRP sheets and plates aids in the transition from shear failure to flexural failure.